Suffering and Salutogenesis: A Conceptual Analysis of Lessons for Psychiatry From Existential Positive Psychology (PP2.0) in the Setting of the COVID-19 Pandemic - Rajkumar, Ravi Philip (Frontiers in Psychology, 2021)
The COVID-19 pandemic has had a widespread effect on the thoughts, emotions and behavior of millions of people all around the world. In this context, a large body of scientific literature examining the mental health impact of this global crisis has emerged. The majority of these studies have framed this impact in terms of pre-defined categories derived from psychiatric nosology, such as anxiety disorders, depression or post-traumatic stress disorder. These constructs often fail to capture the complexity of the actual experiences of the individuals being studied; they describe these experiences exclusively in terms of disease, while neglecting their potentially adaptive or “salutogenic” aspects. Similarly, discussion of psychological assistance for these individuals has largely been confined to a reiteration of “evidence-based” psychological or pharmacological techniques which can be delivered using remote access technology. In the context of the COVID-19 pandemic, these approaches are likely to be of mixed efficacy. Conversely, “negative emotions” or distressing psychological experiences may actually be functional in the setting of a disaster or crisis, serving to minimize harm, maximize social coherence and compliance, and facilitate adherence to safety measures. The limitations of the “conventional” approach are, to a certain degree, inherent to the prevailing medical model of mental health. Beyond these considerations lies the concept of “salutogenesis”, a term which refers to the innate capacity of individuals to create and maintain health and well-being in the face of adversity. Using principles derived from the second wave of positive psychology (PP2.0), particularly its emphasis on the totality of human experience and the possibility of deriving meaning and character growth from suffering, this paper conceptually analyzes the relevant aspects of salutogenesis and PP2.0, and proposes an alternate approach for addressing mental health concerns during the COVID-19 pandemic. Such an approach, while acknowledging the utility of the conventional medical model in specific cases, reduces the risk of medicalizing human experience, and provides individuals and communities with opportunities for growth and adaptation. The benefits of this proposal could potentially extend far beyond the current crisis, offering an opportunity for the field of psychiatry to move away from a purely “disease-centered” model.